Irene Dalis Scrapbook
Irene Dalis as the Küsterin in Jenůfa, possibly sung in Berlin Germany at the Berlin Stadtische Oper. She is holding a doll that depicts the baby her character murders in the opera. The role of Küsterin was responsible for launching her international career.